Methods and Means of a Law Angles Tomography Diagnostics of Ionic Flows of Space Apparatus Engines. (2017) - Phylonin, Oleg
Abstract: Methods, algorithms and means of few projections spectral and tomographic diagnostics of parameters of plasma flows, such as space distribution of local temperatures, concentration, etc. of small-size plasma ejectors (engines of orientation, low thrust) are described.